A Critical Discourse Analysis Approach to Othering: Depiction of the Syrian Refugee Experience in Turkish Children’s Literature - Neslihan Kansu Yetkiner ([sic])
This paper is a critical examination of discursive strategies of othering in three refugee-focused books in Turkish children’s literature written after the onset of Syrian civil war. Drawing upon Van Dijk’s ideological analysis, eliciting the representation of “us vs. them” in a network of semantic and formal structures, the study has two closely related main aims. The first is to show how children’s literature, as a significant conveyor of norms, values, and ideology, provides fertile ground to examine power relations. The second is to identify discursive strategies of othering, which categorize and underscore group-based differences by attributing negative characteristics, in three Turkish children’s books about the Syrian war. Findings demonstrate that negative representation of the Other is foregrounded by actor description, lexicalization, and implicitness within the framework of semantic structures. Formal structures resonate with topoi under the umbrella of argumentation and rhetoric, with special emphasis upon allegory.